Research Advances in the field of Forest Inventory, Biometrics and Growth Modelling Contributing to Forest Management in India - Tewari, V. P. (Indian Forester, 2021)
The discipline of Forest Inventory has developed a versatile toolbox of techniques and methods useful for national level assessments. Forest mensuration has always played an important role in the practice of forest management. Forest measurements and biometrics involves developing and testing methods for taking and using measures from forested lands. Forest management is concerned with future effects of current decisions. The key to successful forest management is a proper understanding of growth processes, and one of the objectives of modelling forest development is to provide the tools that enable foresters to compare alternative silvicultural treatments. In this article, a brief description of Forest inventory and assessment in India, and recent advances made by various ICFRE research institutes in the field of forest mensuration, biometrics and growth modelling leading to effective forest management options has been presented. Research needs and gaps, and suggestions for future research are also given.